Kebijakan Politik United Malay National Organization (UMNO) dalam Perkembangan Islam di Malaysia 1981-2003 M: Political Policy of the United Malay National Organization (UMNO) in the Development of Islam in Malaysia 1981-2003 AD - Nurul Hasanah (Nur Science Institute, 2022)
United Malay National Organization (UMNO) is a political organization that serves as a forum for Malaysian people to express their main aspirations in an effort to fight British colonialism in Malay lands. The policy of the Malayan Union by the British government actually ignited the spirit of the Malay community to oppose the policy through UMNO. Malaysia as a multi-ethnic, racial and religious country indirectly demands the government to be fair in making policies so as not to cause friction even though it is dominated by the Muslim community. This problem is studied using a political approach to government with Carl Friedrich's policy theory. The research method used is the historical method which includes 4 stages; heuristics, verification, interpretation, and historiography. This study found that UMNO's political policy to be pro-Islamic encouraged the development of Islam which was marked by the establishment of Islamic research institutes, Islamic Teacher Schools, International Islamic University (IIUM), Islamic Banks, Islamic Insurance and Islamic Pawnshops. Thus, Islam becomes the foundation for Malaysian society in everyday life because the values of Islamic teachings are embedded in every individual.